Asphalt wearing course optimization for road traffic noise reduction. (15th October 2017) - Vaitkus, Audrius; Andriejauskas, Tadas; Vorobjovas, Viktoras; Jagniatinskis, Aleksandras; Fiks, Boris; Zofka, Ewa
Highlights: The aim of this study is to optimize AC and SMA mixtures for noise reduction. Developed low noise asphalt mixtures for severe climate conditions. Simulation of low noise asphalt mixtures resistance to frost-thaw cycles. Recommended air void content for low noise asphalt mixtures in cold regions. Abstract: Nowadays traffic noise and air pollution are as important as durability parameters, what leads to the need of more comprehensive approach when planning, designing, constructing and maintaining road pavements. Having in mind country differences in traffic volumes, climate conditions and financial capabilities it is not easy to transfer various solutions from country to country. Due to such peculiarities, large research study was initiated in Lithuania seeking to develop efficient and effective low noise pavement solution for specific regional climate conditions. This paper presents research of commonly used asphalt concrete (AC), stone mastic asphalt (SMA), porous asphalt (PA) and a concept of noise reducing asphalt mixtures. As part of this study large scale laboratory testing of acoustical and mechanical performance, durability and resilience to climate were performed. The paper also presents analysis of laboratory testing results which were positive and followed with the pilot implementation of developed asphalt mixtures for further research activities under real traffic and climate conditions.